PERBAIKAN VARIETAS BAWANG MERAH (Allium ascallonicum L) MELALUI PERSILANGAN - Sartono Putrasamedja (Universitas Muhammadiyah Purwokerto, 2010)
This study aims to find the derivative of F1 which will be developed through klon. The research clones carried the glass house Vegetable Crops Research Center of Lembang start March to December 2007. Materials consist of : clone no. 2003/3, klon 2003/5, klon 418, Tiron, Ilokos, SHD, India, Cokol Green, clone no.9, onion leaves and Maja. The final results obtained 1) Plant interest that should be a little late flowering at the age of 30 days after flower plant. 2) Persentase be very low ranging from 5-10%. 3) High rates ranged between 40-50 %. 4) The combination yield obtained from 66 hybrid combinations of F1 seeds weighing an average of 0,1-1,9 grams. Key word : Shallot, hybriditation, colon, F1